2007
DOI: 10.1509/jmkr.44.4.529
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Consumer Learning for Service Quality and Usage

Abstract: This article is based on the first author's doctoral dissertation at Columbia University. The two coauthors are his dissertation advisors. The authors thank the other dissertation committee members (Kamel Jedidi, Yuxin Chen, and K. Sudhir) for their extensive comments and suggestions. The first author thanks Z. John Zhang for insightful discussions. The authors also thank Carl Mela and the Teradata Center at Duke University for providing the data. Finally, the authors thank the Marketing Science Institute for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 23 publications
(27 reference statements)
3
100
1
1
Order By: Relevance
“…They used conjoint data to estimate the model parameters, and then used a grid search to compute the optimal plans numerically. Iyengar Ansari, and Gupta (2007) analyzed data from a single wireless service provider. They developed a model for plan choice and consumption that incorporates consumers' usage uncertainty and consumers' learning for service quality and usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used conjoint data to estimate the model parameters, and then used a grid search to compute the optimal plans numerically. Iyengar Ansari, and Gupta (2007) analyzed data from a single wireless service provider. They developed a model for plan choice and consumption that incorporates consumers' usage uncertainty and consumers' learning for service quality and usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A final alternative assumes that consumers choose a target quantity that is implemented with an exogenous error (Iyengar et al 2007, Jiang 2012. For comparison, our model of consumer choice can be reinterpreted as choice of a target quantity implemented with an endogenous error.…”
Section: Related Literaturementioning
confidence: 99%
“…Knowledge about customers is actually the basis of the CRM approach and it is essential for correct customer segmentation and customer treatment consequently reducing the risk to do business with loss making customers. Better resource allocation and increased market intelligence also result from customer learning (Iyengar et al, 2007). The quantification of nonfinancial effects is needed in order to make them comparable to financial measures.…”
Section: A Literature Review Of the Customer Lifetime Value Conceptmentioning
confidence: 99%
“…Further, through the learning process resources can be allocated in a more adequate way attributing fixed costs of specific products or services more precisely. Iyengar et al (2007) investigated consumer learning for service quality and usage in wireless service. They found that consumer learning can result in a win-win situation for both customers and the company due to less minutes spent by the customers and an increase of 35% of the overall CLV.…”
Section: The Effects Of the Customer Learning Potential On The CLVmentioning
confidence: 99%
See 1 more Smart Citation